2005
DOI: 10.1093/aob/mci255
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Variation in the Silicon Composition of Plants

Abstract: A high shoot Si concentration is not a general feature of monocot species. Information on the phylogenetic variation in shoot Si concentration may provide useful palaeoecological and archaeological information, and inform studies of the biogeochemical cycling of Si and those of the molecular genetics of Si uptake and transport in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
776
9
34

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 929 publications
(852 citation statements)
references
References 38 publications
33
776
9
34
Order By: Relevance
“…In general, angiosperms accumulate more phytoliths in their shoots than gymnosperms. Within the angiosperms, the Poaceae accumulate more phytoliths than other monocot species [41]. Whether different plants yield differing amounts of PhytOC, and what factors control this in each remain to be found.…”
Section: Phytoliths and Phytocmentioning
confidence: 98%
“…In general, angiosperms accumulate more phytoliths in their shoots than gymnosperms. Within the angiosperms, the Poaceae accumulate more phytoliths than other monocot species [41]. Whether different plants yield differing amounts of PhytOC, and what factors control this in each remain to be found.…”
Section: Phytoliths and Phytocmentioning
confidence: 98%
“…According to BRAGA et al (2009), the different behaviour observed in species that receive Si can be explained by the fact that the in vitro growth conditions depends on the development of culture media protocols that are optimized for each species and the perfect interaction of components. Most of the studies involving the effect of Si in the plant was carried out with accumulating species, like the monocots, due to important responses that these plants show in the presence of this element, behaviour that is not often observed for other species, such as those of group of dicots (HODSON et al, 2005). Studies using non-accumulating species of Si have become more frequent due to the larger quest for understanding the behaviour of these plants in the presence of this element, when compared to the wealth of information that already exists about the Si accumulation in Poaceae family (ZHU & GONG, 2014).…”
Section: Phytotechnical Analysismentioning
confidence: 99%
“…Ponzi and Pizzolongo [36] have described the morphology and distribution of epidermal phytoliths in Triticum aestivum. Some other silicon-related aspects in various plants have also been discussed earlier by various active researchers [15,16,21,32,47].…”
Section: Introductionmentioning
confidence: 83%
“…spectrometer. The spectrometer has three modules to provide high resolution (FWHM 0.1 nm) in the 200-500 nm (12,13), sinuous rod shaped (14,15), stomata (16) and epidermal cell (17)] and stem of wheat [elongate sinuous phytolith (18,19), rod shaped (20), trapezoid (21,22), stomata (23), papillae (24), epidermal cell (25)] wavelength region and a fourth module that has low resolution (FWHM 0.75 nm) in the 200-900 nm wavelength region. To record the LIBS spectra we first dried the wheat plants and converted them to powder, and then one gram of powder from each part was used to prepare the pellets.…”
Section: Libs Experimentsmentioning
confidence: 99%